DIGITAL EMPLOYEE EXPERIENCE, WELLBEING 2.0 DAN KINERJA KARYAWAN PADA ORGANISASI DENGAN SISTEM KERJA HYBRID: STUDI LITERATUR - Maria Helena Carolinda Dua Mea; Ega Leovani (ANALISIS, 2026)
Digital transformation and the implementation of hybrid work systems have changed the way organizations manage human resources. Digital Employee Experience (EX) has become a strategic factor affecting employee wellbeing (Wellbeing 2.0) and performance. This study aims to analyze the relationship between digital EX, Wellbeing 2.0, and employee performance through a systematic literature review of scientific publications from 2015 to 2025. The findings indicate that digital EX plays a crucial role in enhancing Wellbeing 2.0 through technology convenience, positive work experiences, and digital support. Wellbeing 2.0 has been shown to act as a mediator that strengthens the impact of EX on performance. This article provides both theoretical and practical contributions for organizations in designing technology-based HR strategies to enhance employee experience and wellbeing.